Analisis Efektivitas Penerapan Standar Pengendalian Mutu (SPM 1) Terhadap Kualitas Audit di Kantor Akuntan Publik (KAP) XY - Devina Nasya Sekar Alea; Arif Fajar Wibisono (Economic Reviews Journal, 2026)
The quality of financial statement audits is fundamentally shaped by the effectiveness of a public accounting firm’s quality control system. This study analyses the effectiveness of Quality Control Standard 1 (SPM 1) implementation and its impact on audit quality at KAP XY, a sole-proprietorship public accounting firm in Yogyakarta, Indonesia. Employing a descriptive qualitative approach, data were gathered through a questionnaire distributed to nine auditors and an in-depth interview with the SPM 1 person-in-charge, supplemented by documentation review of working papers, SPM documents, and the ATLAS audit software. The analytical framework traces three dimentions: (1) the actual mechanism of SPM’s six mandatory elements; (2) the effectiveness of SPM 1 in ensuring audit compliance with Auditing Standards (SA); and (3) KAP XY’s efforts to achieve and sustain audit quality across eight IAPI (2018) indicators. Finding reveal that all six SPM 1 elements have been implemented in a structured and documentable manner. Four elements – leadership responsibility, professional ethics and independence, client acceptance, and monitoring and remediation – operate fully effectively. Two elements – human resources and engagement execution – require further strengthening due to structural constraints inherent to sole-proprietorship firms, particularly the difficulty of maintaining EQR independence during peak season. All nine responders agreed with all statements across the eight audit quality indicators. Five key driving factors and five inhibiting factors were identified. The study concludes that firm scale does not preclude quality compliance, provided leadership commitment and internal mechanism function consistently and substantively.